Integrating multi-wet laboratory diagnostics to study staphylococci in animals in Uganda - Kakooza, Steven; Eneku, Wilfred; Nabatta, Esther; Wampande, Eddie M.; Ssajjakambwe, Paul; Wanyana, Mariam; Munyiirwa, Damien F. N.; Ndoboli, Dickson; Namuyinda, Dorcus; Athieno, Grace; Kayaga, Edrine; Okwasiimire, Rodney; et al. (BMC Microbiology, 2024)
Background Several diagnostic environments in Uganda lack real-time, robust and high-throughput technologies for comprehensive typing of microbes, which is a setback to infectious disease surveillance. This study combined various wet laboratory diagnostics to understand the epidemiology of pathogenic staphylococci isolated from animals in Uganda and the implications for global health security priorities. Methods A retrospective study was conducted employing records and pathogenic staphylococci (from animals) archived at the Central Diagnostic Laboratory (CDL), Makerere University, Uganda, between January 2012 and December 2019. The bacteria were speciated by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and tested for virulence factors [beta lactamases, lecithinase, deoxyribonuclease (DNase), haemolysins] and resistance to ten antimicrobials of clinical and veterinary relevance. Tetracycline and methicillin resistance genes were also tested. Results The prevalent diseases were mastitis in cattle and skin infections in dogs. Of the 111 staphylococci tested by MALDI-TOF MS, 79 (71.2%) were Staphylococcus aureus, 27 (24.3%) were Staphylococcus pseudintermedius and 5 (4.5%) were Staphylococcus schleiferi. All these strains expressed haemolysins. The prevalence of strains with lecithinase, penicillinase, cephalosporinase and DNase was 35.9% (14/39), 89.7% (35/39), 0.0% (0/39) and 87.2% (34/39), respectively. Staphylococci were primarily resistant to early penicillins (over 80%), tetracycline (57.7%), and chloramphenicol (46.2%). Minimal resistance was noted with cloxacillin (0.0%), ciprofloxacin (9.6%), and cefoxitin (3.8%). The prevalence of multidrug resistance (MDR) was 78.8% for general staphylococci, 82.2% for S. aureus, 73.1% for S. pseudintermedius, and 60.0% for S. schleiferi. Multidrug resistant staphylococci were significantly more prevalent in the cattle isolates than in the dog isolates (P < 0.05). The prevalence of methicillin-resistant staphylococci (MRS) tested by resistance to cefoxitin and mecA carriage was 3.8%. These four strains were all isolated from dog skin infections. The tetK gene was the most predominant (35.4%), followed by tetM (25.0%). Conclusion In resource-constrained settings, the approach of integrated diagnostics promises sustainable disease surveillance and the addressing of current capacity gaps. The emergence of MRS (zoonotic bacteria) in companion animals creates a likelihood of reduced treatment options for related human infections, a threat to global health.